PENGUKURAN KUALITAS PERBANKAN SYARIAH SEBAGAI UPAYA DALAM PENINGKATAN KESETIAAN NASABAH - Hayu Wikan Kinasih; Wikan Isthika; Melati Oktafiyani (Jurnal Akuntansi Indonesia, 2019)
The banking industri in Indonesia is growing rapidly nowadays. To support their operating system, the banking industriapplies dual-banking system. It is a system where banking serves two kinds of service to the society, that is conventional and sharia.The dual-banking system aim to give them an alternative choice of banking service so that it will increase the growth of financing in the national economic sector. The more customer of theIslamic bank, the more financing activity can be done. As a new comer in the banking industri, Islamic bank should compete with the incumbent of this industri, that is conventional bank. The important aspect to compete with the competitor is service quality. Furthermore, with the high satisfaction and trust of customers on the service of the Islamic bank, the more they will recommend to the society for having a transaction in Islamic bank so that it will help the growth of Islamic banks. This study learns about the customer’s assessment of the service quality of Islamic banks in Indonesia. Data were obtained randomly using a questionnaire instrument that adopted from the research of Siddiqi and Amin. The result of this research that analyzed using an ordinary least square model (OLS) shows that the variable of service quality and customer satisfaction significantly effect on customer loyalty of Islamic banks.